Improving the Quality of Public Services through Bureaucratic Reformation: Human Right Perspectives - Riri Tasi (Jurnal HAM, 2022)
This article discusses Bureaucratic Reform from the Perspective of Human Rights in improving the quality of public services. Bureaucratic Reform is a process of change that is carried out in stages, systematically, and continuously. It aims to create clean governance, improving public services, capacity, and accountability of bureaucratic performance and professionalism of Human Resource Apparatus. This process can be seen as a change from the current condition to the targeted condition within the scope of Bureaucratic Reform. There are several problems faced in improving maximum public services, including 1) transactions leadership, 2) adaptive organizational structure, 3) weak policy implementation, 4) inefficient organizational structure and management, 5) unclear service systems and strategies, 6) corrupt organizational behavior; 7) lack of transparency. In order to solve problems in the government bureaucracy, it is necessary to reform its structure and work culture. If bureaucratic reform in services is successfully implemented, public service bureaucratic reformation will achieve the expected goals, including: an increase in public respect for government performance as a service provider, a decrease or even elimination of public authority abuse by officials in the agencies concerned; realization of a country that has the most-improved bureaucracy and improves the quality of each service sector to the public.